2016
DOI: 10.1016/j.brachy.2016.04.354
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Urinary Retention after Hdr Brachytherapy as Monotherapy for Prostate Cancer

Abstract: prostate volume (D90), has been used as a measure of implant quality. Although a D90O130 Gy is considered adequate, various studies have shown that a D90$140 Gy is associated with improved biochemical control. Previous studies have found that specific factors such as prostate volume, post implant prostatic edema, and the number of seeds can influence D90. Identifying factors that lead to suboptimal dosimetric outcomes is important in order to improve implant quality as well as clinical outcomes. In this retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similarly, the data on dose-related genitourinary dysfunction has been controversial, and whilst some studies suggested a correlation between dose to the bladder and genitourinary toxicity [ 23 , 24 , 35 41 ], this has generally been unconfirmed by other authors [ 26 ], including the current study in univariable regression analysis ( p = 0.4). This inconsistency may be due to confounding differences in treatment scheme (target volume, position during treatment, bladder volume variation, technique, dose), patient characteristics, grading scale and the length of follow-up [ 42 44 ].…”
Section: Discussionmentioning
confidence: 51%
“…Similarly, the data on dose-related genitourinary dysfunction has been controversial, and whilst some studies suggested a correlation between dose to the bladder and genitourinary toxicity [ 23 , 24 , 35 41 ], this has generally been unconfirmed by other authors [ 26 ], including the current study in univariable regression analysis ( p = 0.4). This inconsistency may be due to confounding differences in treatment scheme (target volume, position during treatment, bladder volume variation, technique, dose), patient characteristics, grading scale and the length of follow-up [ 42 44 ].…”
Section: Discussionmentioning
confidence: 51%